One-dimensional Dynamics for a Discontinuous Singular Mapand the Routes to Chaos - Alexanian, Moorad
We visit a previously proposed discontinuous, two-parameter generalization of the continuous, one-parameter logistic map and present exhaustive numerical studies of the behavior for different values of the two parameters and initial points x0. In particular, routes to chaos exist that do not exhibit period-doubling whereas period-doubling is the sole route to chaos in the logistic map. Aperiodic maps are found that lead to cobwebs with x = ±∞ as accumulation points, where every neighborhood contains infinitely many points generated by the map.
Keywords: Physics